Educational audiology handbook - Johnson, Cheryl DeConde; Seaton, Jane B. (Plural Publishing, Inc., 2021)
Educational Audiology Handbook, Third Edition, offers a roadmap for audiologists who work in schools or other providers who support school-based audiology services. As the gold standard text in the field, the handbook provides guidelines and blueprints for creating and maintaining high-quality educational audiology programs. Educational audiologists will also find guidance for achieving full integration into a school staff. Within this comprehensive and practical resource, there are a range of tools, including assessment guidelines, protocols and forms, useful information for students, families, school staff, and community partners, as well as legal and reference documents. New to the Third Edition All chapters revised to reflect current terminology and best practices A new feature called "Nuggets from the Field" which offers practical information from experienced educational audiologists currently working in school settings Revised and updated chapter on legislative and policy essentials Latest perspectives on auditory processing deficits Contemporary focus on student wellness and social competence Expanded information and resources for access to general education Updated perspectives on hearing loss prevention New information on the development of remote audiology practices Materials and recommendations to support interprofessional collaboration Updated and more comprehensive technology information with multiple handouts and worksheets Resources for students in all current learning environments Expanded focus on coaching to support students and school staff